Calculation:

Consider, the equation, \(\displaystyle{y}={12}-{5}{x}\),

To compute x-intercept, put \(\displaystyle{y}={0}\).

\(\displaystyle{0}={12}-{5}{x}\)

Subtract by 12, this gives,

\(\displaystyle{0}-{12}={12}-{5}{x}-{12}\)

\(\displaystyle-{12}=-{5}{x}\)

Divide the equation by -5,

\(\displaystyle{\frac{{-{5}{x}}}{{-{5}}}}={\frac{{-{12}}}{{-{5}}}}\)

\(\displaystyle{x}={\frac{{{12}}}{{{5}}}}\)

So, the x-intercept is \(\displaystyle{\left({\frac{{{12}}}{{{5}}}},{0}\right)}\).

To compute y-intercept, put \(\displaystyle{x}={0}\).

\(\displaystyle{y}={12}-{5}{\left({0}\right)}={12}\)

So, the y-intercept is(0,12).

Hence, the x and y-intercepts of \(\displaystyle{y}={12}-{5}{x}{\left({\frac{{{12}}}{{{5}}}},{0}\right)}\) and(0,12),respectively.

Consider, the equation, \(\displaystyle{y}={12}-{5}{x}\),

To compute x-intercept, put \(\displaystyle{y}={0}\).

\(\displaystyle{0}={12}-{5}{x}\)

Subtract by 12, this gives,

\(\displaystyle{0}-{12}={12}-{5}{x}-{12}\)

\(\displaystyle-{12}=-{5}{x}\)

Divide the equation by -5,

\(\displaystyle{\frac{{-{5}{x}}}{{-{5}}}}={\frac{{-{12}}}{{-{5}}}}\)

\(\displaystyle{x}={\frac{{{12}}}{{{5}}}}\)

So, the x-intercept is \(\displaystyle{\left({\frac{{{12}}}{{{5}}}},{0}\right)}\).

To compute y-intercept, put \(\displaystyle{x}={0}\).

\(\displaystyle{y}={12}-{5}{\left({0}\right)}={12}\)

So, the y-intercept is(0,12).

Hence, the x and y-intercepts of \(\displaystyle{y}={12}-{5}{x}{\left({\frac{{{12}}}{{{5}}}},{0}\right)}\) and(0,12),respectively.